Religion, a Major Driver for Forced Internationalization - Ergin, Hakan; de Wit, Hans (International Higher Education, 2019)
Today's global phenomenon of forced displacement, at a record high since World War II, has resulted in refugees struggling for access to higher education around the world. Refugees form an untraditional category among international students and force policy makers to employ uncommon drivers to both support their access to universities and handle any possible local societal tensions. Using the case of Syrian refugees' access to higher education in Turkey, this article discusses how religious motivation can enhance refugees' access to higher education in a host country.